2018
DOI: 10.3390/agronomy8120297
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal Variation in Starch Accumulation and Starch Granule Size in Cassava Genotypes in a Tropical Savanna Climate

Abstract: The information on genotypic responses to the seasonal variation in the starch content, starch yield, and starch quality of cassava is limited. The objective of this research was to investigate the seasonal variation of starch characteristics of three cassava genotypes grown under irrigation. The experiment was conducted at four planting dates (20 April, 30 June, 5 October, and 15 December 2015). Three cassava genotypes (CMR38-125-77, Kasetsart 50, and Rayong 11) were evaluated in a randomized complete block d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
21
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 45 publications
1
21
0
Order By: Relevance
“…The positive impacts of effective on-farm management, soil fertility enhancement (organic and inorganic fertilizer applications) and the allocation of suitable lands on cassava yields have been reported in some Sub-Sahara African countries 5,[24][25][26][27]30,58 . One of the major factors responsible for increased cassava yield in Niger, Malawi, Ghana, and Cameroon is effective on-farm management such as mulching and soil tillage 29 . Other factors accounting for increased yield in these countries include the dedication of suitable (fertile) land to cassava cultivation and the use of fertilizer where required 52,53,[59][60][61] .…”
Section: Geospatial Relationship Between Cassava Yield and Environmenmentioning
confidence: 99%
See 1 more Smart Citation
“…The positive impacts of effective on-farm management, soil fertility enhancement (organic and inorganic fertilizer applications) and the allocation of suitable lands on cassava yields have been reported in some Sub-Sahara African countries 5,[24][25][26][27]30,58 . One of the major factors responsible for increased cassava yield in Niger, Malawi, Ghana, and Cameroon is effective on-farm management such as mulching and soil tillage 29 . Other factors accounting for increased yield in these countries include the dedication of suitable (fertile) land to cassava cultivation and the use of fertilizer where required 52,53,[59][60][61] .…”
Section: Geospatial Relationship Between Cassava Yield and Environmenmentioning
confidence: 99%
“…cassava production requires the following conditions: well-drained sandy-loamy/loamy soils, evenly distributed but slightly high annual rainfall amount, moderately high temperature, and long sunshine hour 3,29 .…”
mentioning
confidence: 99%
“…These authors reported that amylose content of the extracted starch was greatly influenced by genotype. Furthermore, higher temperature and solar radiation received during October and December of the growing period resulted in significantly higher starch yield and starch content compared to those planted in other periods of the year (Janket et al, 2018). Some authors similarly found significant variation in the pasting properties of two varieties of bitter yam .…”
Section: Introductionmentioning
confidence: 97%
“…Several factors such as processing methods, growing conditions and genotypic differences may influence the composition and physicochemical properties of cassava flour and starch. For instance, Janket et al, (2018) studied the effect of varying seasons on starch accumulation and starch granule size in cassava genotypes grown in tropic Savana climate. These authors reported that amylose content of the extracted starch was greatly influenced by genotype.…”
Section: Introductionmentioning
confidence: 99%
“…Several factors such as processing methods and variables, growing conditions and genotypic differences may influence the composition and physicochemical properties of cassava flour and starch. For instance, Janket et al [7] studied the effect of varying seasons on starch accumulation and starch granule size in cassava genotypes grown in tropic Savannah climate. These authors reported that amylose content of the extracted starch was greatly influenced by genotype.…”
Section: Introductionmentioning
confidence: 99%